2021
DOI: 10.51577/jhqd.v1i1.99
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Lingkungan Kejadian ISPA Pada Balita di Wilayah Kerja Puskesmas Panambungan

Abstract: Acute respiratory infections (ARI) is a disease that attacks one or more parts of the respiratory tract from the nose to the alveoli or lung. This disease which is caused by various factors (multifactorial) is the top rank disease in Indonesia, and is the biggest cause (17%) of the death of children under five years (toddlers). This study aims to determine the environmental risk factors for the incidence of ARI in children under five in the working area of the Panambungan Health Center. This type of research u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[10] Other studies have also found that exposure to cigarette smoke is associated with the incidence of pneumonia in children. [7,10,12,17,18] In one metaanalysis study, the smoking behavior of family members has the highest risk as a cause of pneumonia in children. [1] 3.…”
Section: Environmental Factors 1 Residential Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Other studies have also found that exposure to cigarette smoke is associated with the incidence of pneumonia in children. [7,10,12,17,18] In one metaanalysis study, the smoking behavior of family members has the highest risk as a cause of pneumonia in children. [1] 3.…”
Section: Environmental Factors 1 Residential Densitymentioning
confidence: 99%
“…[7] The use of wood or charcoal as cooking fuel and the use of burnt mosquito repellents were also found to be significantly associated with the incidence of acute respiratory infections (ARI) in children. [18] In addition, using only cement or earth as a floor for a house can also increase the risk of ARI in children because during the dry season the floor will produce a lot of dust which can interfere the respiratory system. [18] House walls made of wood and woven bamboo also make it easier for dust to stick and children who live in the house with non-permanent walls are found to be more at risk of suffering from pneumonia.…”
Section: Pollution In the Housementioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, the number of cases of acute respiratory infection (ARI) is very high and ranks in the top ten of the most common diseases (Nur, 2021). ISPA is one of the main causes of patient visits to health facilities, namely 40% to 60% of all visits to puskesmas and 15% to 30% of all outpatient and inpatient visits to hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Dari kunjungan berobat di puskesmas maupun rumah sakit dan 15%-30% kunjungan berobat di rumah sakit. Gejala yang sering dijumpai adalah batuk, pilek, dan kesukaran bernafas yang dapat menimbulkan akibat kematian [6]. ISPA dapat dibagi menjadi dua bagian yaitu ISPA atas dan ISPA bawah.…”
unclassified